Recovery of Pt (IV) from aqueous solutions using magnetic functionalized cellulose with quaternary amine. Issue 8 (24th May 2019) - Yousif, Ahmed M.; Labib, Sherif A.; Ibrahim, I.A.; Atia, Asem A.
ABSTRACT: A new magnetic cellulose hybrids anchored with quaternary amine moieties were fabricated and used in recovering Pt(IV) ions from acidic solutions. Kinetic and thermodynamic parameters of adsorption process were reported through using batch experiments. An equilibrium uptake capacity of 178 mg g −1 was achieved within 55 min. The adsorption process was found to follow the pseudo-second-order kinetics and fitted well Langmuir and D-R adsorption isotherms revealing monolayer surface coverage and physisorption mechanism, respectively. At low pH values and high chloride concentration ranges, ion exchange was proposed as the predominant mechanism for the adsorption of Pt(IV) ions on the sorbent. The obtained sorbent showed good durability, easy separation, and regeneration from the adsorption medium.